Реалистик тасвир ва бадиий маҳорат - Матякупов, С (SCIENCE and SOCIETY, 2016)
The article deals with the issues of realistic analysis of literary skill in Uzbek prose. There were also analysed the writer‘s style, his mastery, crea- tive individuality on the basis of concrete examples on the basis of the analysis of artistic peculiarities of the creative activity of Nazar Eshankul.
Keywords: individuality; literary interpretation; literary; idea; philosophic interpretation